The Effect of Cattle Manure Application and Bulb Tip Cutting on the Growth and Yield of Shallots (Allium ascalonicum L.) - Martuani Hasibuan; Rasmita Adelina; Erwin Syah Lubis; Sutan Pulungan (International Journal of Natural Science Studies and Development (IJOSS), 2026)
This study aimed to examine the effects of cow manure application and bulb tip cutting on the growth and yield of shallots (Allium ascalonicum L.). The observed parameters included plant height, number of leaves, number of bulbs per clump, fresh weight, dry weight, bulb diameter, and weight loss after storage. The results showed that the application of cow manure had a significant effect on early plant growth, particularly on plant height at 14 days after planting (p < 0.05), and also affected the number of leaves and bulbs per clump at manure doses of 50 g/polybag (A1), 100 g/polybag (A2), and 150 g/polybag (A3) compared to the control (A0). The bulb tip cutting treatment significantly influenced growth at ¼ (B1) and ⅓ (B2) cutting levels compared to no cutting, especially in the number of leaves and shoot emergence rate. The interaction between cow manure and bulb tip cutting also showed a significant effect. The best combination was obtained in A2B1 (100 g/polybag of cow manure + ¼ bulb tip cutting), which produced an average plant height of 39.17 cm, an average of 32.33 leaves at 35 days after planting, an average fresh bulb weight per clump of 159.67 g, and an average dry bulb weight per clump of 107.16 g. Therefore, this combination treatment can be recommended as a simple cultivation technique to enhance shallot productivity in low-fertility soils